2014
DOI: 10.1002/gcc.22220
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant TP53 detected by combining immunohistochemistry and DNA‐FISH improves Barrett's esophagus progression prediction: A prospective follow‐up study

Abstract: Barrett's esophagus (BE) goes through a sequence of low grade dysplasia (LGD) and high grade dysplasia (HGD) to esophageal adenocarcinoma (EAC). The current gold standard for BE outcome prediction, histopathological staging, can be unreliable. TP53 abnormalities may serve as prognostic biomarkers. TP53 protein accumulation detected by immunohistochemistry (IHC) indirectly assesses TP53 mutations. DNA fluorescent in situ hybridization (FISH) on brush cytology specimens directly evaluates gene locus loss. We eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Surprisingly, the size of the biggest clone, evidenced by p53 loss and/or p53 relative locus loss was not a prognostic marker. Thus, in this cohort of BE patients with no dysplasia, p53 loss did not bear prognostic potential, which is in contrast to findings in Barrett cohorts that also included patients with low- and high-grade dysplasia16202122. We included the significant prognostic markers in a multivariate model with age and circumferential Barrett's length (accepted prognostic factors232425) and found that all eight genetic variables were the most significant predictors of progression (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Surprisingly, the size of the biggest clone, evidenced by p53 loss and/or p53 relative locus loss was not a prognostic marker. Thus, in this cohort of BE patients with no dysplasia, p53 loss did not bear prognostic potential, which is in contrast to findings in Barrett cohorts that also included patients with low- and high-grade dysplasia16202122. We included the significant prognostic markers in a multivariate model with age and circumferential Barrett's length (accepted prognostic factors232425) and found that all eight genetic variables were the most significant predictors of progression (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 71%
“…3). In contrast, p53 loss observed in at least 5% of the cells was found in only 7.5% of patients ( n =24), and relative p53 locus loss16 (defined by copy-loss or fewer copies of the p53 locus relative to the chr17 centromere (Methods)—observed in more than 5% of cells was seen in 10.6% of patients ( n =34). In addition, comparison of the data from multiple brushes collected at the same endoscopy (termed repeat brushes) validated the reproducibility of our FISH analysis (Methods and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The FISH analysis as performed in this study may have underestimated p53 losses, since p53 locus loss may also occur in cells with genetic instability and gains for chromosome 17, which could lead to ‘copy neutral loss of heterozygosity’. [30,31] Also, point mutations leading to abnormal p53 function were undetectable by our methods. Other discrepancies might be due to differences in detection methods.…”
Section: Discussionmentioning
confidence: 89%
“…A more precise clinical test would be p53 fluorescent in situ hybridization which is less widely available and has increased cost. 39 Other commonly involved genes in Barrett’s esophagus include p16 abnormalities as well as evidence of chromosomal instability both of which could be assessed with immunohistochemistry and FISH respectively. These tests may better stratify risk of progression though data supporting their use to date are limited.…”
Section: Discussionmentioning
confidence: 99%